A “NEW” FEMALE IMAGE IN OL’HA SLONIOVS’KA’S NOVEL “UPOLIOVANE POKOLINNIA” - Fotuima І. V. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2019)
The article makes an attempt of analysing a woman’s new type in Ukrainian literature, the woman, who makes a life for herself, can stand up for herself. The evolution of a female image, its author’s interpretation through the prism of personal perception are traced.